2014
DOI: 10.1016/j.ccr.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous Metastasis of Ovarian Cancer: Rethinking Mode of Spread

Abstract: SUMMARY Ovarian cancer has a clear predilection for metastasis to the omentum, but the underlying mechanisms involved in ovarian cancer spread are not well understood. Here, we used a parabiosis model that demonstrates preferential hematogenous metastasis of ovarian cancer to the omentum. Our studies revealed that the ErbB3-neuregulin1 (NRG1) axis is a dominant pathway responsible for hematogenous omental metastasis. Elevated levels of ErbB3 in ovarian cancer cells and NRG1 in the omentum allowed for tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
286
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(294 citation statements)
references
References 32 publications
6
286
0
2
Order By: Relevance
“…By screening a panel of growth factors and their cognate receptors in TAMs and spheroid-associated tumor cells, we have identified the EGF/EGFR regulatory pathway that is critical for TAM-stimulated OC proliferation and cancer progression. A previous study reported that EGFR expression increased significantly in free tumor cells compared with implanted tumor cells in the peritoneal cavity, suggesting that the EGFR pathway plays an important role in peritoneal free tumor cells (46). It is well known that the peritoneal cavity contains abundant macrophages and T lymphocytes in the ascites of OC patients (47).…”
Section: 7mentioning
confidence: 98%
“…By screening a panel of growth factors and their cognate receptors in TAMs and spheroid-associated tumor cells, we have identified the EGF/EGFR regulatory pathway that is critical for TAM-stimulated OC proliferation and cancer progression. A previous study reported that EGFR expression increased significantly in free tumor cells compared with implanted tumor cells in the peritoneal cavity, suggesting that the EGFR pathway plays an important role in peritoneal free tumor cells (46). It is well known that the peritoneal cavity contains abundant macrophages and T lymphocytes in the ascites of OC patients (47).…”
Section: 7mentioning
confidence: 98%
“…These findings are a compelling verification of the 'seed and soil' hypothesis (21), which claims compatibility of colonization with the corresponding target tissues. Recently, this currently held assumption of nonhematogenous spread of ovarian cancer metastasis was challenged by employing a parabiosis model in which two living mice were joined together to develop a shared circulatory system (22). In this model, preferential metastasis of ovarian cancer to the omentum was mediated by the interaction between human epidermal growth factor receptor 3 (HER3) expressed on ovarian cancer cells and its ligand neuregulin 1 (NRG1) expressed by cells in the omentum, allowing tumor homing to as well as growth in the omentum (22).…”
Section: General Issues Of Pathogenesis Of Ovarian Cancermentioning
confidence: 99%
“…Recently, this currently held assumption of nonhematogenous spread of ovarian cancer metastasis was challenged by employing a parabiosis model in which two living mice were joined together to develop a shared circulatory system (22). In this model, preferential metastasis of ovarian cancer to the omentum was mediated by the interaction between human epidermal growth factor receptor 3 (HER3) expressed on ovarian cancer cells and its ligand neuregulin 1 (NRG1) expressed by cells in the omentum, allowing tumor homing to as well as growth in the omentum (22). Ovarian cancer cells can also spread via ovary-draining lymphatics to pelvic and para-aortic lymph nodes, but this mode of dissemination is rare.…”
Section: General Issues Of Pathogenesis Of Ovarian Cancermentioning
confidence: 99%
“…Besides intraperitoneal seeding, recent results demonstrated that EOC cells are able to metastatize hematogenously (37). Therefore to metastasize, EOC cells acquire the ability to invade surrounding tissues and intravasate to enter the systemic circulation.…”
Section: Macitentan Sensitizes Eoc Xenografts To Chemotherapeutic Drugsmentioning
confidence: 99%